(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Shift work is a prevalent practice in various industries, essential for maintaining continuous operations and services. However, an increasing body of research indicates that shift work can have significant adverse effects on workers’ health. This review examines the current literature on the impact of shift work on physical and mental health outcomes. The findings suggest a strong association between shift work and increased risks of cardiovascular disease, gastrointestinal disorders, metabolic syndrome, sleep disturbances, and mental health issues such as depression and anxiety. The review also explores the mechanisms underlying these health effects and discusses potential interventions to mitigate the negative consequences of shift work.